Eligibility for and prescription of urate-lowering treatment in patients with incident gout in England - Kuo, Chang-Fu; Grainge, Matthew J.; Mallen, Christian; Zhang, Weiya; Doherty, Michael (American Medical Association, 2014)
Gout is caused by urate crystal deposition secondary to persistent hyperuricemia. Current guidelines recommend urate-lowering treatment to prevent crystal deposition and encourage crystal dissolution for patients with more severe gout or concomitant conditions.1,2 However, after the first diagnosis, it remains unclear when such treatment is appropriate. We investigated the timing of eligibility for and prescription of urate-lowering treatment following first gout diagnosis and factors associated with prescription.